119 Palatability of Olive Pomace in Mozambique Tilapia (Oreochromis mossambicus). (28th November 2020) - Krasue, Ethan; Conn, Benny J; Kelley, Stanley F; Beverly, Marcy M; Anderson, Mark
Abstract: By-products, such as distillers' and brewers' dried grains, are used in livestock rations as a source of important nutrients, cheapen feed costs, and reduce the cost of production. Olive pomace is the by-product from the production and milling of olive oil, and is a possible source of protein and energy for livestock. The objective of this study was to determine if Mozambique tilapia would consume olive pomace when mixed with commercial feed. Sixty tilapia of similar size were divided into two separate tanks, each with its own aquaponic filtration system. Ammonia, pH, nitrates, nitrites, and chlorine levels were monitored to ensure optimum water environment. Olive pomace, from a two-phase mill, has a slurry-like constancy containing approximately 50% moisture. Due to its high moisture content, the pomace was offered to the fish in a dried state and mixed with a commercial feed at a 1:1 ratio. The dried pomace immediately sank to the bottom of the tank while the commercial feed remained on the water surface and consumed by the fish. The rate of consumption of the dried pomace could not be separated from the tank sediment, and therefore was not measurable. To deter the pomace from sinking, wet pomace was mixed at a 1:1 ratio with the floating commercial feed. The wet pomace, mixed well with the commercial feed and yielded a consistent blend of pomace and feed. The moist pomace:feed blend was molded by hand into 2 ½ centimeter spheres, each weighing approximately 9.1 grams. Four spheres were dropped into each tank allowing multiple fish to feed at once. Although, the wet blended feed mixture did not float, the fish ate the feed spheres as they sank. This preliminary research illustrates the willingness of tilapia to consume olive pomace and its potential use as a feed.